2018
DOI: 10.3389/fevo.2018.00101
|View full text |Cite
|
Sign up to set email alerts
|

How Bats Escape the Competitive Exclusion Principle—Seasonal Shift From Intraspecific to Interspecific Competition Drives Space Use in a Bat Ensemble

Abstract: Predators that depend on patchily distributed prey face the problem of finding food patches where they can successfully compete for prey. While the competitive exclusion principle suggests that species can only coexist if their ecological niches show considerable differences, newer theory proposes that local coexistence can be facilitated by so-called stabilizing and equalizing mechanisms. A prerequisite to identify such mechanisms is the understanding of the strength and the nature of competition (i.e., inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 68 publications
1
37
1
Order By: Relevance
“…Another, not mutually exclusive explanation for the comparable low feeding buzz rate may be that even distribution of prey items across the forest dominated landscape led to lower prey density at small scales, when compared to insect rich patches above the cropland dominated landscape. Both explanations suggest that common noctules flying above the forested landscape may have mainly competed for prey (Cvikel et al , Roeleke et al ), whereas bats flying above cropland might have been limited by the search for scarce food patches, but not by the competition for single food items within such insect rich patches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another, not mutually exclusive explanation for the comparable low feeding buzz rate may be that even distribution of prey items across the forest dominated landscape led to lower prey density at small scales, when compared to insect rich patches above the cropland dominated landscape. Both explanations suggest that common noctules flying above the forested landscape may have mainly competed for prey (Cvikel et al , Roeleke et al ), whereas bats flying above cropland might have been limited by the search for scarce food patches, but not by the competition for single food items within such insect rich patches.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, past studies showed that foraging efficiency of bats can be impaired at high densities (Amichai et al ). Bats might thus avoid aggregations of conspecifics (Roeleke et al ) or even engage in agonistic behaviour when competing for prey (Voigt‐Heucke et al , Corcoran and Conner ). Interestingly, an individual's recent feeding activity had no influence on the probability to switch from DM to ARM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insectivorous bats Nyctalus noctule (noctule) and Nathusius’ pipistrelle ( Pipistrellus nathusii ; Roeleke et al. ) are among many other species which have been observed to exhibit exploitative competition, including mudsnails (Hybroiidae; Fenchel and Kofoed ); wild dog ( Lycaon pictus ), spotted hyena ( Crocuta crocuta ), and lion ( Panthera leo ); Caro and Stoner ). Exploitative competition is difficult to measure without controlled removal experiments, which are exceedingly difficult with bats (Clare et al.…”
Section: Introductionmentioning
confidence: 99%